Rapid evaluation method for performance of solid electrolyte reactor

By measuring the conductivity of the extracted water in a solid electrolyte reactor and calculating the formic acid concentration using mathematical fitting formulas, the problem of complicated characterization of formic acid production performance of solid electrolyte reactors in the prior art is solved, and a fast and accurate performance evaluation is achieved.

CN119881022APending Publication Date: 2025-04-25FUJIAN AGRI & FORESTRY UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510114067.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, the performance characterization of formic acid production in solid electrolyte reactors depends on cumbersome and time-consuming analytical methods, such as nuclear magnetism or liquid chromatography, which makes it impossible to quickly assess reactor performance.

Method used

By preparing a series of concentrations of formic acid solution and determining its conductivity, mathematically fitting the concentration of the formic acid solution and its conductivity, the fitting formula is obtained. Then, the extract liquid is introduced into the solid electrolyte reactor, the reactor is run and the extract liquid effluent is collected, and its conductivity is measured. The formic acid concentration fitted using the conductivity is calculated using the fitting formula, and the Faraday efficiency is calculated to quickly characterize the reactor performance.

Benefits of technology

It realizes rapid assessment of the performance of solid electrolyte reactors, reduces experimental steps and time, and improves the accuracy and efficiency of the evaluation method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119881022A_ABST
    Figure CN119881022A_ABST
Patent Text Reader

Abstract

The invention discloses a rapid characterization method for the performance of a solid electrolyte reactor for formic acid preparation through carbon dioxide reduction, which comprises the following steps: establishing a mathematical relationship between formic acid concentration and conductivity in a series of formic acid solutions, rapidly fitting the formic acid concentration of effluent of an extracting solution in the solid electrolyte reactor, and then calculating Faraday efficiency. Therefore, the performance of the solid electrolyte reactor is judged. The method can realize rapid evaluation of the performance of the solid electrolyte reactor for formic acid production through carbon dioxide reduction, and is also suitable for rapid evaluation of the performance of solid electrolyte reactors for producing acetic acid, hydrogen peroxide, ammonia and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemistry and carbon dioxide utilization, and particularly relates to a method for quickly evaluating the performance of a solid electrolyte reactor for preparing formic acid by reducing carbon dioxide. Background Art

[0002] One of the most promising approaches to address the challenges of global climate change is electrochemical carbon capture and utilization (CCU). Solid electrolyte reactors are a promising technology in the field of CCU. Different from traditional H-type reactors, flow cells, membrane electrode assemblies (MEAs), etc., solid electrolyte reactors are additionally equipped with an extraction chamber filled with solid electrolytes, thereby realizing a variety of extended functions. For example, solid electrolyte reactors can achieve carbon dioxide capture or improve carbon utilization without adding chemicals. In addition, solid electrolyte reactors can also be applied to carbon dioxide electrochemical reduction reaction (CO2RR), carbon monoxide electrochemical reduction reaction (CORR), and nitric oxide electrochemical reduction reaction (NORR) to achieve production and extraction of reduction products, such as charged anions such as formic acid, acetic acid, hydrogen peroxide, and ammonia, and neutral molecules such as ethanol can also be extracted through diffusion and other effects. It is worth noting that the most commonly used extraction liquid in solid electrolyte reactors is deionized water, because one of the primary applications of solid electrolyte reactors is to achieve the acquisition of pure liquid products. Secondly, a local high concentration of products can be formed on the solid electrolyte interface, which is conducive to further reaction of the extracted products in situ. For example, the local high concentration of H2O2 formed at the solid electrolyte interface promotes the efficient conversion of olefins to produce ethylene glycol. In addition, these pure liquid products can be used as substrates for biocatalysts such as enzymes and microorganisms, avoiding the problem of high concentrations of salt mixed into the products of traditional electrochemical reactors and causing inhibition. Therefore, solid electrolyte reactors have promoted the development of electrochemical microbial coupling technology in the field of high-value utilization of carbon dioxide.

[0003] It is worth noting that the production of formic acid in solid electrolyte reactors has received widespread attention. In terms of the economic return per unit electron input, formic acid is a good target end product. In addition, electrochemical microbial coupling technology usually uses formic acid as an intermediate product to connect the electrochemical system and the biological conversion system. This is because liquid formic acid can avoid the gas-liquid mass transfer limitations caused by CO, H2, etc. Although acetic acid and ethanol, as intermediate products, connect the electrochemical system and the biological conversion system, can provide higher reducing power and can also serve as substrates for more types of microorganisms, at this stage, CO2RR only has high selectivity and current density in the production of C1 substances such as formic acid. Even for CORR with CO as a substrate, its performance in producing acetic acid and ethanol needs to be improved. It can be seen that the production of formic acid in solid electrolyte reactors has broad application prospects in the fields of electrochemistry and carbon dioxide utilization technology, but its performance characterization often relies on cumbersome and time-consuming analytical methods. Traditional formic acid concentration determination methods, such as nuclear magnetic resonance or liquid chromatography (HPLC), although highly accurate, require filtration, dilution, and weighting with water, and rely on large instruments and equipment. The operation is complex and time-consuming, which is not conducive to the rapid characterization of the formic acid production performance of solid electrolyte reactors. Therefore, the development of a fast and accurate characterization method is of great significance to promote the research and application of solid electrolyte reactors. Summary of the invention

[0004] The present invention aims to provide a method for quickly evaluating the performance of a solid electrolyte reactor for preparing formic acid by reducing carbon dioxide.

[0005] To achieve the above object, the present invention adopts the following technical solution: A method for rapidly evaluating the performance of a solid electrolyte reactor comprises the following steps: 1) Prepare formic acid solutions with a series of concentrations and measure their conductivity, then perform mathematical fitting on the concentration of the formic acid solution and its conductivity to obtain a fitting formula; 2) introducing the extract into the solid electrolyte reactor, and operating the solid electrolyte reactor in a constant current or constant pressure mode (preferably in a constant current mode), collecting the effluent of the extract and measuring its conductivity, and then calculating the formic acid concentration using the conductivity fitting using the fitting formula obtained in step 1); 3) Using the formic acid concentration obtained by the conductivity fitting in step 2) as a parameter, the Faraday efficiency (FE) based on the conductivity fitting formic acid concentration is calculated using the Faraday efficiency calculation formula, thereby quickly determining the performance of the solid electrolyte reactor.

[0006] The solid electrolyte reactor is specifically used in the reaction of reducing formic acid using carbon dioxide, and includes an extraction chamber filled with a solid electrolyte, an anode chamber for introducing an anode liquid, a gas chamber for introducing carbon dioxide, and a cathode arranged between the gas chamber and the extraction chamber for catalyzing carbon dioxide reduction, and an anode arranged between the anode chamber and the extraction chamber for catalyzing an oxygen evolution reaction.

[0007] Furthermore, the extraction solution is introduced into an extraction chamber filled with a solid electrolyte.

[0008] Furthermore, the solid electrolyte filled in the extraction chamber is an ion exchange resin.

[0009] Furthermore, the cathode surface, the side facing the extraction chamber, is covered with an anion exchange membrane or filter paper or other materials as a diaphragm to improve the catalytic performance.

[0010] Furthermore, pure water or an inorganic acid solution is introduced into the anode chamber as the anode liquid to prevent other cations (such as Na + , K + ) migrates from the anode chamber to the extraction chamber.

[0011] Furthermore, the anode plate used in the anode chamber should be stable to prevent the release of cations (such as Fe 2+ , Fe 3+ ), and migrate from the anode chamber to the extraction chamber.

[0012] Furthermore, the surface of the anode, the side facing the extraction chamber, is covered with a cation exchange membrane to prevent inorganic anions in the anode chamber from migrating from the anode chamber to the extraction chamber.

[0013] Furthermore, the solvent used to prepare the series of formic acid solutions in step 1) should be consistent with the extracting solution used in the solid electrolyte reactor. Preferably, the extracting solution is deionized water, and accordingly, the solvent used to prepare the formic acid solution is also deionized water. This is because deionized water is the most commonly used extracting solution in the solid electrolyte reactor. In the present invention, the use of deionized water can also avoid the excessive background value affecting the measurement accuracy when the conductivity is measured.

[0014] Furthermore, when the solid electrolyte reactor in step 2) is in operation, the formic acid concentration in the effluent of the extract can be adjusted by controlling the current density, voltage or flow rate of the extract. For example, the current density is 10-300 mA / cm 2 , the voltage is 3-15 V, and the obtained formic acid concentration is 0-100 g·L -1 .

[0015] Furthermore, the Faraday efficiency calculation formula in step 3) is: , in: F is the Faraday constant, 2 is the number of electron transfers to produce formic acid, x To fit the formic acid concentration (M), V is the flow rate (L·s -1 ), I is the current (A), t is the running time (s).

[0016] The significant advantages of the present invention are: 1. The present invention provides a method for rapidly evaluating the performance of a solid electrolyte reactor, and by examining the agreement between the formic acid concentration measured by high performance liquid chromatography (HPLC) and the formic acid concentration fitted by conductivity, and the Faraday efficiency based on the formic acid concentration measured by HPLC and the Faraday efficiency based on the formic acid concentration fitted by conductivity, it is confirmed that the method can realize the rapid evaluation of the performance of a solid electrolyte reactor for producing formic acid by reducing carbon dioxide.

[0017] 2. The present invention can improve the accuracy of the characterization method by optimizing measures such as the selection of solvents when making formic acid-conductivity marking lines, the separation measures between the anode chamber and the extraction chamber, the selection of the anode liquid, and the stability of the anode plate in the anode chamber.

[0018] 3. The method of the present invention can also be applied to the rapid characterization of the performance of solid electrolyte reactors such as acetic acid production, hydrogen peroxide production, and ammonia production. It is only necessary to equip the solid electrolyte reactor with a cathode having a corresponding catalytic function, and use the corresponding product standard solution concentration and conductivity for mathematical fitting. Other reactor operating parameters may also change. For example, in order to achieve efficient acetic acid production, CO can be introduced into the gas chamber as a substrate for the electrochemical reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is the mathematical fitting result of formic acid concentration and conductivity in formic acid standard solution in a specific embodiment of the present invention.

[0020] Figure 2 It is a schematic structural diagram of a solid electrolyte reactor for producing formic acid by reduction of carbon dioxide in a specific embodiment of the present invention, wherein: 1-gas chamber; 2-cathode; 3-diaphragm; 4-solid electrolyte; 5-extraction chamber; 6-extraction liquid inlet; 7-cation exchange membrane; 8-anode; 9-anode chamber.

[0021] Figure 3 The degree of agreement between the formic acid concentration determined by HPLC and the formic acid concentration obtained by conductivity fitting for the effluent of the extract collected by running a solid electrolyte reactor equipped with different anodes and filled with different types of solid electrolytes in a specific embodiment of the present invention.

[0022] Figure 4The degree of agreement between the Faraday efficiency of formic acid concentration measured by HPLC and the Faraday efficiency of formic acid concentration fitted based on conductivity is shown in Figure 2, which is a graph of the results of running a solid electrolyte reactor equipped with different anodes and filled with different types of solid electrolytes and collecting the extracted water in a specific embodiment of the present invention.

[0023] Figure 5 In a specific embodiment of the present invention, the solid electrolyte reactor with different types of filter papers covering the surface of the gas diffusion electrode is operated and the effluent of the extract is collected. The degree of agreement between the formic acid concentration determined by HPLC and the formic acid concentration obtained by conductivity fitting is determined.

[0024] Figure 6 In a specific embodiment of the present invention, the solid electrolyte reactor is operated with different types of filter papers on the surface of the gas diffusion electrode and the extract effluent is collected. The degree of agreement between the Faraday efficiency of the formic acid concentration measured by HPLC and the Faraday efficiency of the formic acid concentration fitted based on conductivity is shown. DETAILED DESCRIPTION

[0025] The present invention proposes a method for rapidly evaluating the performance of a solid electrolyte reactor. The method first uses formic acid solutions of a series of concentrations and corresponding conductivities to perform mathematical fitting to obtain a fitting formula. Then, in the solid electrolyte reactor, the reactor is operated by controlling the fluid flow rate and electrochemical conditions, and an extract from which formic acid products are extracted is collected for conductivity measurement. The obtained fitting formula is then used to calculate the formic acid concentration corresponding to the conductivity, and the Faraday efficiency is further calculated to rapidly characterize the formic acid production performance of the solid electrolyte reactor.

[0026] This method is also applicable to the rapid characterization of the performance of solid electrolyte reactors for producing acetic acid, hydrogen peroxide, ammonia, etc. It is only necessary to equip the solid electrolyte reactor with a cathode having a corresponding catalytic function and use the corresponding product standard solution concentration and conductivity for mathematical fitting.

[0027] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings.

[0028] Example 1 In this embodiment, combined with Figure 1 , the mathematical fitting of formic acid concentration and conductivity in a formic acid standard solution in a specific embodiment of the present invention is described.

[0029] Deionized water was used to prepare formic acid solutions of a series of concentrations (0-2 M), and the conductivity of the obtained formic acid solutions was measured with a conductivity meter. Then, the formic acid concentration x and its corresponding conductivity y were mathematically fitted, and the optimal fitting formula obtained was y=a*x^b, where a=147.988, b=0.524, R 2 =0.999.

[0030] Example 2 In this embodiment, combined with Figure 2-4 , the operation of a solid electrolyte reactor equipped with different anodes and filled with different types of solid electrolytes at different current densities in a specific embodiment of the present invention is described.

[0031] The solid electrolyte reactor includes a gas chamber for introducing carbon dioxide, an extraction chamber filled with solid electrolyte, an anode chamber for introducing anolyte, a cathode disposed between the gas chamber and the extraction chamber, and an anode disposed between the anode chamber and the extraction chamber. The cathode is a gas diffusion electrode (area 4 cm2) in a sandwich configuration, which is formed by spraying a nano-bismuth catalyst (particle size 50 nM) on hydrophobic carbon paper with an airbrush as a catalyst layer, and is combined with a cationic layer and a protective layer. 2 , its preparation method is shown in patent CN 119243201A), the cathode surface is covered with whatman No. 1 filter paper as a diaphragm; the extraction chamber is filled with 0.67 g of different types of hydrogen-type strong acid cation exchange resin as a solid electrolyte (IRC120H or 50WX2), and the anode is platinum-coated titanium felt (Pt) or iridium-coated titanium felt (Ir). The extraction solution is deionized water, and its unidirectional flow rate is 0.05 mL·min -1 The anolyte was 100 mL of 0.5 M H2SO4 solution and the flow rate was controlled at 2 ml min -1 , CO2 was introduced into the gas chamber and the flow rate was controlled at 50 ml·min -1 The solid electrolyte reactor was operated at different current densities (50, 100, 150, 200 mA·cm -2 ) was operated at a constant current to regulate the formic acid concentration in the effluent water of the extract, and then the effluent water of the extract was collected separately, the formic acid concentration therein was determined by HPLC, and the conductivity was determined by a conductivity meter, and the formic acid concentration fitted by conductivity was obtained according to the formula x=(y / a)^(1 / b), and then the Faraday efficiency based on the formic acid concentration measured by HPLC and the Faraday efficiency based on the formic acid concentration fitted by conductivity were calculated respectively according to the following formulas.

[0032] , in: F is the Faraday constant, 2 is the number of electron transfers to produce formic acid, x is the formic acid concentration (M), V is the flow rate (L·s -1 ), I is the current (A), t is the running time (s).

[0033] The results showed that the formic acid concentration in the extract was affected by different types of solid electrolytes and anodes. Due to the low flow rate of the extract, its formic acid concentration fluctuated in the range of 400-1700 mM. The formic acid concentration measured by HPLC and the formic acid concentration fitted by conductivity were highly consistent, with an error of 0.2%-12.3%. Considering that the two paired samples of formic acid concentrations met the normal distribution, the paired sample t-test was used, and it was found that there was no significant difference between the two at the 0.05 level. The Faraday efficiency based on the formic acid concentration measured by HPLC and the Faraday efficiency based on the formic acid concentration fitted by conductivity were also highly consistent, with an error of 0.2%-12.3%. Considering that the two paired samples of Faraday efficiency met the normal distribution, the paired sample t-test was used, and it was found that there was no significant difference between the two at the 0.05 level.

[0034] Example 3 In this embodiment, combined with Figure 4 and Figure 5 , the operation of a solid electrolyte reactor in which the surface of a gas diffusion electrode is covered with filter papers of different types in a specific embodiment of the present invention is described.

[0035] The cathode is a gas diffusion electrode (area 4 cm) with a sandwich structure consisting of a nano-bismuth catalyst (particle size 50 nM) sprayed on hydrophobic carbon paper with an airbrush as a catalyst layer, a cationic layer and a protective layer. 2 ), the surface of the gas diffusion electrode was covered with different types of filter paper (whatman No. 1, whatman No. 2, whatman No. 4, whatman No. 6, whatman No. 43), the extraction chamber was filled with 0.67 g of hydrogen-type strong acid cation exchange resin as a solid electrolyte (IRC120H), and the anode was platinum-coated titanium felt (Pt). The extraction solution was deionized water, and its unidirectional flow rate was 0.26 mLmin -1 The anolyte was 100 mL of 0.5 M H2SO4 solution and the flow rate was controlled at 2 ml min -1 The gas chamber was filled with CO2 and the flow rate was controlled at 50 ml min -1 The solid electrolyte reactor was operated at different current densities (15, 30, 60, 90, 120, 150 mA·cm -2 ) was operated at a constant current to regulate the formic acid concentration in the effluent water of the extract, and then the effluent water of the extract was collected separately, the formic acid concentration therein was determined by HPLC, and the conductivity was determined by a conductivity meter, and the formic acid concentration fitted by conductivity was obtained according to the formula x=(y / a)^(1 / b), and then the Faraday efficiency based on the formic acid concentration measured by HPLC and the Faraday efficiency based on the formic acid concentration fitted by conductivity were calculated according to the following formulas.

[0036] , in: F is the Faraday constant, 2 is the number of electron transfers to produce formic acid, x is the formic acid concentration (M), V is the flow rate (L·s -1 ), I is the current (A), t is the running time (s).

[0037] The results showed that the formic acid concentration in the extract was affected by different types of filter paper. Due to the high flow rate of the extract, its formic acid concentration fluctuated in the range of 0-400 mM. The formic acid concentration measured by HPLC and the formic acid concentration fitted by conductivity were highly consistent, with an error of 0.1%-17.9%. Considering that the two paired samples of formic acid concentration were not normally distributed, the paired sample Wilcoxon test was used, and it was found that there was no significant difference between the two at the 0.05 level. The Faraday efficiency based on the formic acid concentration measured by HPLC and the Faraday efficiency based on the formic acid concentration fitted by conductivity were also highly consistent, with an error of 0.1%-17.9%. Considering that the two paired samples of Faraday efficiency met the normal distribution, the paired sample t test was used, and it was found that there was no significant difference between the two at the 0.05 level.

[0038] Although the present invention has been described in detail, modifications within the spirit and scope of the present invention will be apparent to those skilled in the art, and the above description is intended only as an example and is not intended to limit the present invention.

Claims

1. A method for rapidly evaluating the performance of a solid electrolyte reactor for producing formic acid by carbon dioxide reduction, characterized in that: The following steps are involved: 1) Prepare formic acid solutions with a series of concentrations and measure their conductivity, then perform mathematical fitting on the concentration of the formic acid solution and its conductivity to obtain a fitting formula; 2) introducing the extract into the solid electrolyte reactor, and operating the solid electrolyte reactor in a constant current or constant pressure mode, collecting the effluent of the extract and measuring its conductivity, and then calculating the formic acid concentration using the conductivity fitting using the fitting formula obtained in step 1); 3) Using the formic acid concentration obtained by the conductivity fitting in step 2) as a parameter, the Faraday efficiency calculation formula is used to calculate the Faraday efficiency based on the formic acid concentration fitted by the conductivity, thereby quickly determining the performance of the solid electrolyte reactor.

2. The method for rapid evaluation of solid electrolyte reactor performance according to claim 1, characterized in that: The solid electrolyte reactor comprises an extraction chamber filled with solid electrolyte, an anode chamber into which anode liquid is introduced, a gas chamber for introducing carbon dioxide, a cathode arranged between the gas chamber and the extraction chamber, and an anode arranged between the anode chamber and the extraction chamber.

3. The method for rapid evaluation of solid electrolyte reactor performance according to claim 2, characterized in that: The solid electrolyte filled in the extraction chamber is ion exchange resin.

4. The method for rapid evaluation of solid electrolyte reactor performance according to claim 2, characterized in that: The cathode surface, the side facing the extraction chamber, is covered with a diaphragm.

5. The method for rapid evaluation of solid electrolyte reactor performance according to claim 2, characterized in that: The anode surface, the side facing the extraction chamber, is covered with a cation exchange membrane.

6. The method for rapid evaluation of solid electrolyte reactor performance according to claim 1, characterized in that: The formic acid solution in step 1) uses the extract used in the solid electrolyte reactor as a solvent.

7. The method for rapid evaluation of solid electrolyte reactor performance according to claim 1, characterized in that: The current density used in the solid electrolyte reactor in step 2) is 10-300 mA / cm 2 , the voltage is 3-15 V.

8. The method for rapid evaluation of solid electrolyte reactor performance according to claim 1, characterized in that: The Faraday efficiency calculation formula in step 3) is: , in: F is the Faraday constant, 2 is the number of electron transfers to produce formic acid, x To fit the formic acid concentration, V is the flow rate, I is the current, t For the running time.

Citation Information

Patent Citations

  • Preparation method and application of sandwich-structured gas diffusion electrode

    CN119243201A

  • Inorganic electrolyte lithium salt content detection method

    CN107807150A

  • Method for producing potassium diformate by electrocatalysis of waste carbon resources

    CN118531415A

  • Method for preparing formic acid / formate through electrocatalytic reduction of carbon dioxide based on metal cation reinforced solid electrolyte

    CN118756170A

  • Electrochemical carbon dioxide reduction device without prefabricated anion exchange membrane and application of electrochemical carbon dioxide reduction device

    CN119243192A